2021
DOI: 10.21203/rs.3.rs-222107/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Negative Capacitance in Partially Ground Plane based SELBOX FET on Capacitance Matching and SCEs

Abstract: Here in, we investigated the impact of negative capacitance in PGP-SELBOX NCFET (partial ground plane on a selective buried oxide in negative capacitance FET) over FDSOI. The ferro-electric layer is placed in the gate stack of PGP-SELBOX NCFET to generate the negative capacitance phenomenon. Ferroelectric(FE) materials are similar to dielectric materials but differ in terms of their polarization properties. FE-HFO 2 is used as ferroelectric material due to its sufficient polarization rate with high dielectric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Given the low sensitivity of the baseline FDSOI device, as shown in earlier, we now include an optimized thickness of the FE layer (optimization discussed in appendix A, figure A1) over the pre-existing DE layer (stack of HfO 2 and SiO 2 ), thus modifying the architecture to an FE-DE stack-based NCFET, which results in effectively increasing the maximum height of the cavity. To include the effects of FE material on the device electrostatics in TCAD simulations, Landau parameters (given by Agarwal et al [58]), as shown in table 3, are used and the L-K equation [59,60] is included in the self-consistent loop of Poisson's, drift-diffusion and current continuity equations, which enables the determination of various channel electrostatic parameters.…”
Section: Impact Of Ferroelectric Layer On Sensitivitymentioning
confidence: 99%
“…Given the low sensitivity of the baseline FDSOI device, as shown in earlier, we now include an optimized thickness of the FE layer (optimization discussed in appendix A, figure A1) over the pre-existing DE layer (stack of HfO 2 and SiO 2 ), thus modifying the architecture to an FE-DE stack-based NCFET, which results in effectively increasing the maximum height of the cavity. To include the effects of FE material on the device electrostatics in TCAD simulations, Landau parameters (given by Agarwal et al [58]), as shown in table 3, are used and the L-K equation [59,60] is included in the self-consistent loop of Poisson's, drift-diffusion and current continuity equations, which enables the determination of various channel electrostatic parameters.…”
Section: Impact Of Ferroelectric Layer On Sensitivitymentioning
confidence: 99%